In Search of Mobile Applications for Patients With Pelvic Floor Disorders. Issue 3 (May 2019) - Sudol, Neha T.; Adams-Piper, Emily; Perry, Rachel; Lane, Felicia; Chen, Katherine T.
Abstract : Objectives: The aims of the study were to identify patient-centered applications (apps) in female pelvic medicine and reconstructive surgery and to evaluate them using a modified APPLICATIONS scoring system. Methods: A comprehensive list of female pelvic medicine and reconstructive surgery search terms was used to identify apps in the iTunes store. Apps that were eligible for scoring were in English, pertinent to the search term, patient centered, and accurate. All five authors independently evaluated eligible apps using a modified APPLICATIONS scoring system and subsequently reconciled differences by discussion. Results: One hundred and fifty-seven terms were generated and searched in the iTunes Store to reveal 4127 apps. Twenty-three eligible apps were scored. Approximately half (47%, 11/23) of the apps were free. Twelve (52%) apps cited scientific literature or expert source. Only 8 (35%) of the apps were also available in the Google Play Store. "Squeezy, " "LeakFreeMe, " and "Stop UTI" received the highest score of 14. Conclusions: Few identified apps were accurate and subsequently scored. Our results demonstrate that when searching for apps, patients are likely to obtain information that is not relevant or inaccurate, even if the appropriate search term is used. By carefully excluding inaccurate apps, providers should feel confident that the 23 scored apps can be shared with patients. Abstract : A modified scoring system was successfully used to rate medically accurate mobile health applications that can be shared with patients with pelvic floor disorders.